Instructions to adopt an external focus enhance muscular endurance - Marchant, D. C.; Greig, M.; Bullough, J.; Hitchen, D. (Research Quarterly for Exercise and Sport, 2011)
The influence of internal (movement focus) and external (outcome focus) attentional-focusing instructions on muscular endurance were investigated using three exercise protocols with experienced exercisers. Twenty-three participants completed a maximal repetition, assisted bench-press test on a Smith's machine. An external focus of attention resulted in significant (p < .05) improvements in performance compared to the internal focus of attention, but not the control condition. Seventeen participants completed repetitions to failure at 75% 1-RM on free bench-press and squat exercises. In both tasks, externally focused instructions resulted in significantly greater repetitions to failure than control and internal focus conditions (p < .05). These results support previous research showing beneficial effects of externally focused instructions on movement efficiency.